At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

solve each equation. check your solution. 4a - 3 (a - 2) = 2(3a - 2)

Sagot :

luana
[tex]4a-3(a-2)=2(3a-2)\ \ \ \ \ \ \ |simplify\\\\4a-3a+6=6a-4\ \ \ \ \ \ \ \ |combine\ like\ terms\\\\4a-3a-6a=-4-6\\\\-5a=-10\ \ \ \ \ |:-5\\\\a=2[/tex]
4a - 3a - 6 = 6a - 4
a  = 6a +2
-5a=2

2/5
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.